Experiential Learning in a Gamified Pharmacy Simulation: A Qualitative Exploration Guided by Semantic Analysis - Denise L. Hope; Gary D. Rogers; Gary D. Grant; Michelle A. King (MDPI AG, 2021)
Experiential learning is an important component of pharmacist education and is primarily achieved through supervised placement or simulation. This study explored senior pharmacy students' experiential learning in an extended, immersive, gamified simulation, conducted as a capstone learning activity toward the end of their final year of study, consolidating all prior learning and preparing students for intern practice. The simulation aimed to enhance student confidence, competence and collaboration. The three-week activity involved student teams competitively managing simulated pharmacies, assuming the role of pharmacists to complete all scaffolded assessments, including dispensing prescriptions, clinical cases, verbal counselling, simulated patient cases, interprofessional collaboration, and assignments. Assessments were marked continuously, with consequences of practice acknowledged through gain or loss of 'patients' for the pharmacy. From 2016 to 2018, 123 students completed multiple individual reflective journals (n = 733). Reflective journals were analyzed to explore the student experience, using a mixed methods approach. Initial Leximancer® 4.51 semantic analysis guided thematic analysis, conducted in NVivo® 12. The major themes that emerged were teamwork, patient-centeredness, medicines provision, future practice, and the learning experience. Student participants reported an intense and emotional experience in the gamified simulation, with many students revealing transformation in their skills, behaviors and attitudes over its duration.